Hermeneutika Al-Qur’an Fazlur Rahman (Studi Pemikiran Fazlur Rahman dan Metodologi Hermeneutikanya) - Putra, Fuad Dwi (Mutiara: Multidiciplinary Scientifict Journal, 2025)
This study will discuss and examine an interpretive tool offered by Fazlur Rahman. Fazlur Rahman is a Muslim scholar who has made significant contributions through his hermeneutic method. The methodical tool employed by Rahman is commonly known as the double movement method. This method is quite well-known and widely discussed among modern-contemporary intellectuals. However, in fact, it is not only the double movement method that is Rahman's mainstay in interpreting the verses of the Qur'an; there is also a method called the logical-synthesis method. In the double movement method, the focus is on legal and social aspects whose application is socio-historical-chronological. Meanwhile, the logical-synthesis method is more directed at verses with metaphysical-theological aspects that have a synthetic-thematic procedure that is logical rather than chronological, which allows for a comprehensive view of the Qur'an. This is what distinguishes this article from other articles, namely Rahman who is only known for his double movement method but forgets that Rahman also has a logical-synthesis method that focuses on verses with metaphysical-theological aspects. In this study, the author used a literature research method. The data obtained were reviewed, analyzed, and presented in a descriptive-analytical manner. The data focused on works related to Fazlur Rahman, both his works such as books and scientific journals, as well as books on thought related to Fazlur Rahman as secondary data. The method offered by Rahman is not a final method and still has weaknesses and shortcomings. It is hoped that Rahman's contribution can be used for the development of scientific knowledge in Islam, especially in this modern-contemporary era, where the problems faced are far more complex.